Islam is a Foreign Country: American Muslims and the Global Crisis of Authority By Zareena Grewal (New York: New York University Press, 2014. 409 pages.) (American Journal of Islam and Society, 2015)
Zareena Grewal’s book traces the hopes, debates, accomplishments, and disappointmentsof American Muslim students who travel to the Middle East inpursuit of Islamic knowledge. As Grewal discovers through her interviewswith over 100 students and teachers, the impetus behind many of their journeysis a desire to find a solution to the “crisis” of Islamic authority in theUnited States. But once they spend some time immersed in a predominantlyMuslim society, many discover that this crisis extends to the Muslim worldas well. More recently, some American Muslim scholars have shifted their attention away from the Middle East and toward an “indigenization” of AmericanIslam, which, the author points out, also faces many challenges.In chapter 1 Grewal explains that her project is focused on student-travelerswho view the Islamic East as an “Archive of Tradition” (p. 36) that they hopewill provide a more authentic and authoritative form of Islamic knowledgethan what they could learn in the United States. Her fieldwork took her toAmman, Damascus, and Cairo during the early 2000s, where she interviewedstudents of such figures as Shaykh Nuh Ha Mim Keller, Qubaysiya AnsaTamara Gray, and Shaykh Ali Goma‘a, among others. The students she metcame from diverse ethnic, geographic, and socio-economic backgrounds. Grewaldoes a good job of highlighting how these factors shaped their journeys ...